Analisis Penerapan Neuroekonomi dalam Pengambilan Keputusan Transaksi dan Investasi pada Mahasiswa Pendidikan Ekonomi Universitas Mulawarman - Ariani, Syifa Tri; Riyo Riyadi; Reza (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
Transaction and investment decision making in students is often influenced by irrational and emotional factors. This can result in suboptimal and risky decisions, which can have negative financial repercussions in the future. The purpose of this study is to find out how the application of neuroeconomics in making transaction and investment decisions of Mulawarman University Economic Education students. This research is a descriptive research with a qualitative approach. Data collection using interviews and observations. Data analysis used is data reduction, data presentation, and verification/conclusions. The informants of this study were 6 students of Economic Education at Mulawarman University. The results of this study show that Mulawarman University Economic Education students apply neuroeconomics in making transaction and investment decisions, students gain knowledge about products by searching for information. Students consider emotional responses to purchasing decisions as well as satisfaction. Investment decisions made by students for the long term and get maximum profit. Different types of investments are compared to choose the type of investment that suits personal finance.